Management Paradigms for an Evolving Future:: Towards Prosperity in the e-Economy - Couturier, Christian (Journal of Comparative International Management)

(untitled) (Management Futures, 2005)
Abstract "A cloud masses, the sky darkens, leaves twist upward, and we know that it will rain. We also know that after the storm, the runoff will feed into groundwater miles away, and the sky will grow clear by tomorrow. All these events are distant in time and space, and yet they are all connected within the same pattern. Each has an influence on the rest, an influence that is usually hidden from view. You can only understand the system of a rainstorm by contemplating the whole, not any individual part of the pattern" (Senge, 1994). This paper follows a keynote presentation and attempts to reflect on the systems view of the present, and the futures that may very well affect how we live as much as how we do business in the global e-economy. As an organization, you are a corporate citizen of the world. You need to pay close attention to the evolution of that world - changes in population, health, education, etc., so you can better understand the impact on your business eco-system. As in Senge's example of the storm, we must consider all the phenomena as being interconnected and inseparable.